Simulations and experimental demonstrations of encoding for X-ray coherent scattering - Prokopiou, Danae; Smith, Kerrie L.; Rogers, Keith; Paula, P.; Evans, Paul; Dicken, Anthony; Godber, S. (International Union of Crystallography, 2017)
Diffraction data may be measured using approaches that lead to ambiguity in the interpretation of scattering distributions. Thus, the encoding and decoding of coherent scatter distributions have been considered with a view to enabling unequivocal data interpretation. Two encoding regimes are considered where encoding occurs between the X-ray source and sample, and where the encoder is placed between the sample and detector. In the first case, the successful recovery of diffraction data formed from the interrogation of powder samples with annular incident beams is presented using a coded aperture approach. In a second regime, encoding of Debye cones is shown to enable recovery of sample position relative to the detector. The errors associated with both regimes are considered and the advantages of combining both discussed.